التخطيط اللغوي في المنظومة التعليمية الجزائرية المرحلة الابتدائية أنموذجا - لعوج, منصورية (كلية الأدب العربي والفنون, 2025)
من المعروف بأنّ اللّغة وسيلة للتواصل وبناء المعرفة وتعد محور أساسي في العمليّة التعليمية، فتدريس القراءة أحد عناصر تعليم اللّغة حيث تبنى من خلالها مهارات عدة كالفهم والتحليل والتذكر، وتدريسها يشكل قاعدة جيّدة لأيّ نظام تربوي يسعى إلى بناء المجتمع واع ومتعلم، ومن هذا المنطلق يأتي التخطيط اللّغوي باعتباره جملة من السياسات والاستراتيجيات التي تساهم في تنظيم استخدام اللّغة، وكيفية التعامل بها بين أفراد المجتمع ، من خلال تحديد اللّغة المناسبة في التعليم وكذلك تطوير المناهج ويوفر التخطيط البيئة المناسبة لتكور اللّغة ونموها ويضمن استخدامها في مختلف المواقف التي تصادفه في حياته اليومية، يهدف التخطيط اللّغوي في الجزائر إلى التوفيق بين الهوية الوطنية والتعدد الثقافي والانفتاح العالمي .It is known that language is a means of communication and building knowledge and is an essential axis in the educational process.Teaching reading is one of the elements of language education, through which several skills are built, such as understanding, analysis, and remembering.Teaching it constitutes a good basis for any educational system that seeks to build a conscious and educated society.From this standpoint, planning comes.Linguistics as a set of policies and strategies that contribute to regulating the use of language and how to deal with it among members of society By identifying the appropriate language in education as well as developing curricula, planning provides the appropriate environment for the language to develop and grow and ensures its use in various situations it encounters in its daily life.Linguistic planning in Algeria aims to reconcile national identity, cultural pluralism and global openness..
Keywords: اللّغة، التخطيط، التخطيط اللّغوي، التعليم، القراءة.